The Hypolimnas misippus Genome Supports a Common Origin of the W Chromosome in Lepidoptera - Orteu, A; McCarthy, SA; Hornett, EA; Gemmell, MR; Reynolds, LA; Warren, IA; Gordon, IJ; Hurst, GDD; Durbin, R; Martin, SH; Jiggins, CD (Oxford University Press, 2024)
Moths and butterflies (Lepidoptera) have a heterogametic sex chromosome system with females carrying ZW chromosomes and males ZZ. The lack of W chromosomes in early-diverging lepidopteran lineages has led to the suggestion of an ancestral Z0 system in this clade and a B chromosome origin of the W. This contrasts with the canonical model of W chromosome evolution in which the W would have originated from the same homologous autosomal pair as the Z chromosome. Despite the distinct models proposed, the rapid evolution of the W chromosome has hindered the elucidation of its origin. Here, we present high-quality, chromosome-level genome assemblies of 2 Hypolimnas species (Hypolimnas misippus and Hypolimnas bolina) and use the H. misippus assembly to explore the evolution of W chromosomes in butterflies and moths. We show that in H. misippus, the W chromosome has higher similarity to the Z chromosome than any other chromosome, which could suggest a possible origin from the same homologous autosome pair as the Z chromosome. However, using genome assemblies of closely related species (ditrysian lineages) containing assembled W chromosomes, we present contrasting evidence suggesting that the W chromosome might have evolved from a B chromosome instead. Crucially, by using a synteny analysis to infer homology, we show that W chromosomes are likely to share a common evolutionary origin in Lepidoptera. This study highlights the difficulty of studying the evolution of W chromosomes and contributes to better understanding its evolutionary origins.